'O daughter … forget your people and your father's house': Early Modern Women Writers and the Spanish Imaginary. Issue 7 (13th September 2016) - Holloway, Anne; Wray, Ramona
Abstract: Holloway and Wray consider the perspectives offered by two very different seventeenth-century women: Mary Bonaventure Browne, or Mother Browne (b. 1615) and Lady Ann Fanshawe (b. 1625) both of whom exchanged Ireland for Spain, and both of whom record journeys both 'real' and imagined in their writings. Browne's deployment of hagiographical tropes in her History of the Poor Clares may reveal the potential impact of Iberian conventual culture; her allusions to the markers of sanctity insistent on the immutability of the body, whilst accepting and anticipating spectral presence in the form of bilocation. Fanshawe's Memoirs are considered alongside the material legacy of her 'Booke of Receipts of Physickes, Salues, Waters, Cordialls, Preserues and Cookery'. Her impressions both in transit and within the domus are similarly marked by receptivity and sensitivity to the host culture. Amidst a backdrop of religious persecution and political uncertainty, in both cases Spain emerges as a potentially enabling context for creativity and self-expression.